Penanaman Bibit Bunga Matahari untuk Meningkatkan Daya Tarik Wisata Budaya Punden Didesa Losari Gondang Nganjuk - Achmad Syaifulloh; Ernik Ernawati; Dita Atasa; Fatchur Rozci; Dhian Satria Yudha; Hendra Maulana (Institut Nalanda, 2023)
Losari Village has quite good and prospective tourism potential if it is managed properly, one of which is by using rainwater as its main source of irrigation, the average farmer changes the type of crop he grows on arid and barren hills to corn. Losari hamlet is a remote hamlet, although it is far from other villages, it is likely to develop into a more sophisticated hamlet than the others. If it is managed properly and effectively, the tourism potential of the hamlet is represented by Sendang Sari, or Mata Air, Punden Losari, Sendang's position Sari is surrounded by many large plants and makes it difficult for the area around Sendang Sari to be exposed to sunlight, so modifications are made including religious tourism in the form of Sendang Sari and Punden Losari. To overcome this problem, therefore village officials planted sunflowers to increase tourist attraction so that they were interested in taking pictures with sunflowers or even just seeing and enjoying the beauty of sunflowers. Through this community service activity in the form of creative and innovative activities, sunflower aims to increase the potential for tourist attraction. The result of the sunflower planting activity at Punden Losari is that it can add to the aesthetic value of the existing cultural tourist attraction, which has been planted with 700 sunflower seeds by adding aesthetic value to Punden Losari and benefiting wild birds in Losari Punden as well. The service team in this innovative activity has played an active role and participated in increasing community synergy so that beautiful natural tourism can be created